Periodontal regeneration: Lessons from the periodontal ligament-cementum junction in diverse animal models - Sone, Eli D.; McCulloch, Christopher A. (Frontiers in Dental Medicine, 2023)
The attachment of the roots of mammalian teeth of limited eruption to the jawbone is reliant in part on the mineralization of collagen fibrils of the periodontal ligament (PDL) at their entry into bone and cementum as Sharpey’s fibers. In periodontitis, a high prevalence infection of periodontal tissues, the attachment apparatus of PDL to the tooth root is progressively destroyed. Despite the pervasiveness of periodontitis and its attendant health care costs, and regardless of decades of research into various possible treatments, reliable restoration of periodontal attachment after surgery is not achievable. Notably, treatment outcomes in animal studies have often demonstrated more positive regenerative outcomes than human clinical studies. Conceivably, defining how species diversity affects cementogenesis and cementum/PDL regeneration could be instructive for informing novel and more efficacious treatment strategies. Here we briefly review differences in cementum and PDL attachment in commonly used animal models to consider how species differences may lead to enhanced regenerative outcomes.